2010
DOI: 10.1161/strokeaha.109.564492
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Stimulates Production of Prostacyclin in Cerebral Arteries

Abstract: Background and Purpose-The role of brain-derived neurotrophic factor (BDNF) and its receptor, tropomyosin receptor kinase B, in control of cerebral circulation is poorly understood. The present study was designed to investigate the cerebral vascular effects of BDNF in vivo. Methods-Replication incompetent adenovirus encoding either rat BDNF (AdBDNF) or green fluorescent protein was injected intracisternally into rabbits. Forty-eight hours later, animals were euthanized. Plasma and cerebrospinal fluid levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…Given the use-dependent nature of both post-stroke angiogenesis 39 and the neurovascular coupling relationship, it is likely that OIS map plasticity, increased vascular density, and behavioral recovery were mutually dependent processes in MEM-treated animals. Regarding mechanism, BDNF signaling is involved in angiogenesis 40,41 , and BDNF polymorphisms, associated with poor stroke outcome in humans, show reduced angiogenesis in animal models 42 . Our peri-infarct BDNF increases may be relevant in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Given the use-dependent nature of both post-stroke angiogenesis 39 and the neurovascular coupling relationship, it is likely that OIS map plasticity, increased vascular density, and behavioral recovery were mutually dependent processes in MEM-treated animals. Regarding mechanism, BDNF signaling is involved in angiogenesis 40,41 , and BDNF polymorphisms, associated with poor stroke outcome in humans, show reduced angiogenesis in animal models 42 . Our peri-infarct BDNF increases may be relevant in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the concentration of serum BDNF reflects the changes in brain BDNF levels[21-23]; therefore, measuring the concentration of serum BDNF can be used to monitor its changes in the brain[24]. It was recently demonstrated that BDNF stimulates the production of prostacyclin in cerebral arteries[25]; it plays an important role in endothelium-dependent relaxation and has also antiplatelet, vasculoprotective, cardioprotective and anti-atherogenic properties[26-28]. Zoladz et al[29] demonstrated that the decrease in serum BDNF levels after hemodialysis is accompanied by elevated levels of F-isoprostanes and decreased plasma total antioxidant capacity, which might be caused by the increase in oxidative stress induced by hemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…Prostacyclin mediates biological actions through its G-protein-coupled receptor (IP receptor), where it is known to cause vasodilation and anti-platelet aggregation as one of the major vasoprotectors [1, 2] and the endocrine systems [3, 4], and is used as a vascular protective agent and treatment option in pulmonary hypertension [5, 6]. Although PGI 2 is known to be generated in cerebral arteries [7, 8], the consequences of increased PGI 2 secretion within central nervous system (CNS) have not been extensively characterized.…”
Section: Introductionmentioning
confidence: 99%